POLICY BRIEF: RATA-RATA LAMA SEKOLAH PENDIDIKAN DASAR DAN UPAYA PENINGKATANNYA DI KABUPATEN ASMAT, PROVINSI PAPUA SELATAN - Hermansyah, Agus Kichi; Nggaruaka, Tobias; Sumarsono, Adi (Program Studi PGSD, FKIP, Universitas Mataram, 2024)
The article explores educational challenges in Asmat Regency, part of South Papua Province, hindered by geographical and social factors. It scrutinizes the educational landscape, emphasizing the low average years of schooling (AYS) and geographical issues affecting access. Data reveals that most Asmat children only reach basic education due to uneven educational distribution and limited transportation access. Influencing factors include a shortage of educators and insufficient school facilities. AYD trend analysis indicates that achieving the mandatory nine years of education is far from the government's target. In response, a policy program is devised to enhance AYS in Asmat, involving dormitory construction, educational aid, scholarships, school building development, staff housing, and teacher and educational staff restructuring. Despite its holistic approach, effective monitoring and evaluation are crucial for successful implementation. Aligned with South Papua's developmental potential, this article aspires that these measures contribute to advancing education accessibility and quality in Asmat Regency